Pengaruh Motivasi, Budaya Kerja dan Fasilitas Kerja terhadap Kinerja Pegawai Dinas Pendidikan dan Kebudayaan Kabupaten Bireuen - Idris, Abdullah; Azhari, Azhari; Abqa, Rizkan (Aceh Cooperative Care, 2023)
Research analyzes the supporting factors from the internal and external aspects of employee performance, namely based on motivation, work culture and work facilities. This study uses an associative method with a type of quantitative approach, with the path analysis method. The instrument uses a questionnaire that has been tested for validity and reliability. The results of the study, simultaneously the variables of work motivation, work culture at the Office of Education and Culture of Bireuen Regency and work facilities have proven to make a positive contribution to employee performance, which is equal to 56.1%. And partially all exogenous variables have a statistical effect on performance, namely: (a). The direct and indirect influence of work motivation on employee performance is 38.56%, (b). The direct and indirect influence of work culture on employee performance is 45.19%, (c). The direct and indirect influence of work facilities on employee performance is 42.13%.